System Dynamics and Frequency Regulation of a Multi-Area Power System Using an Optimal Controller (International Journal of Innovative Research in Engineering & Management, 2022)
For system frequency control, the  current work proposes a multi-area power system  integrating various renewable sources. An effective  controller with intrinsic superior capabilities of restricting  peak deviation, steady state errors, and oscillatory  behavior of a dynamic system is an apparent alternative  for autonomous generation control of interconnected  power systems. The most difficult part of using a  controller is figuring out how to get the most out of it.  Because of its space complexity, the trial and error  method of determining the benefit by indirect  optimization with an acceptable performance index  appears to be insufficient. As a result, it appears that  using an effective algorithm technique to find the  maximum gains for the controllers is the best option. The  gains of the controllers are addressed in this work and  thus are optimized using a meta-heuristic technique in  this study.
Keywords: Power system; Optimal Controller; Thermal solar; Thermal wind